Weak and Strong Merging of Opinions - Ehud Kalai; Ehud Lehrer (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
We study merging, in a few senses, of two measures when increasing sequence of information is observed. Motivating this extension of Blackwell and Dubins' (1962) work, are studies of convergence to equilibrium in infinite games and in dynamic economies.
Keywords: 330